1985
DOI: 10.1901/jaba.1985.18-249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stimulus Preference and Reinforcer Value With Profoundly Retarded Individuals

Abstract: We evaluated a procedure for identifying potential reinforcers with profoundly retarded individuals. In Experiment 1, six persons were repeatedly exposed to 16 stimuli, and approach behaviors to each stimulus were used to identify preferred and nonpreferred stimuli. In Experiment 2, we examined the reinforcing properties of preferred and nonpreferred stimuli by delivering them contingently on the occurrence of arbitrarily selected responses. Results revealed that the preferred stimulus conditions typically pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
411
1
8

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(431 citation statements)
references
References 11 publications
11
411
1
8
Order By: Relevance
“…Prior to the study, five preferred items were identified for each individual via both single-presentation (Pace, Ivancic, Edwards, Iwata, & Page, 1985) and paired-stimulus (Fisher et al, 1992) preference assessments. Items approached on at least 80% of the trials during the single-presentation assessment, on at least 50% of the trials during the paired-stimulus assessment, or both, were identified as preferred stimuli; of these items, the five stimuli with the highest percentages of approach responses were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the study, five preferred items were identified for each individual via both single-presentation (Pace, Ivancic, Edwards, Iwata, & Page, 1985) and paired-stimulus (Fisher et al, 1992) preference assessments. Items approached on at least 80% of the trials during the single-presentation assessment, on at least 50% of the trials during the paired-stimulus assessment, or both, were identified as preferred stimuli; of these items, the five stimuli with the highest percentages of approach responses were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The technology for allowing persons with intellectual disabilities to choose from among two or more items, often referred to as preference assessments, has steadily advanced over the past 20 years (DeLeon & Iwata, 1996;Fisher et al, 1992;Pace, Ivancic, Edwards, Iwata, & Page, 1985). However, preference assessments usually allow people to choose only from among items that can be placed in one's hand or on a table top (e.g., toys, candy, etc.).…”
Section: How Can Recipients Of Behavior-change Procedures Bementioning
confidence: 99%
“…A number of applied studies have been conducted in recent years on stimulus preference procedures and have demonstrated the effectiveness of assessing preference for stimuli prior to using them as reinforcers to both increase (Pace, Ivancic, Edwards, Iwata, & Page, 1985) and decrease (Steege et al, 1989) behavior. In light of the present results, which clearly indicated that preference in one context may not predict preference in another, it appears that the variables that affect choice in applied settings, and the extent to which assessing reinforcing efficacy in one context is predictive of reinforcer efficacy in another, are in need of further investigation.…”
Section: Effort Manipulationmentioning
confidence: 99%